Phytochemicals and Antioxidant of Seaweed Tea Padina Australis - Rachmawati, Nandya Fitri; Nuryanti, Ika Faiz; Adharani, Nadya (Institut Teknologi Sepuluh Nopember, 2021)
seaweed contains bioactive compounds that can be used to support human health. One of the seaweeds that are widely found in Indonesia is seaweed / brown algae. An example of brown algae, one of which is Padina australis. Padina australis is a seaweed that contains many bioactive compounds, such as alkaloids, flavonoids, saponins, tannins, and antioxidants. However, Padina australis is not widely applied and used in processed food products. So in seaweed research, Padina australis is used as seaweed tea. In this study, Padina australis seaweed tea was carried out the difference in length of immersion with hot water and the treatment of immersion time is 0 minutes, 5 minutes, 10 minutes, and 15 minutes. The bioactive compounds studied are alkaloids, flavonoids, saponins, tannins, and antioxidant activity. The results showed that the difference in immersion time there are bioactive components in the form of phytomias contained in Padina australis tea, among others: alkaloids, flavonoids, tannins, and saponins in each treatment (0 minutes, 5 minutes, 10 minutes, and 15 minutes). In the test the highest antioxidant activity on P4 treatment (15 minutes) was 47.7% and for the lowest on treatment P2 (5 minutes) by 44.8%.